STRATEGI PENGEMBANGAN PRODUK TERHADAP LOYALITAS PELANGGAN MELALUI EKUITAS MEREK DAN CITRA MEREK - Nur Hakim, Bagus; Purwoko, Bambang (SEKOLAH PASCASARJANA PRESS, 2019)
Product quality, brand equity and brand image are assumed to possess an important role in developing customer loyalty since brand product that has good quality will make the customer loyal. This study is made to find out how far the influence of product quality, brand equity and brand image perception to the loyality of the Nexcare Acne Cover product customer is and what dominant variable that influences customer loyalty. This study is held to 290 consumers of anti acne product of Nexcare Acne Cover. The data processing for this research is Structural Equation Model (SEM) Smart PLS. The study result shows that quality product have influence to brand equity and brand image in Indomaret, Guardian and carrefour, in Guardian brand equity doesn’t have influence to brand image and customer loyalty, brand image have influence to customer loyalty in Indomaret, Guardian and Carrefour. The dominant influence in each account are brand image at Indomaret and Guardian, brand equity at Carrefour.